The Importance of Education in Developing Future Employees’ and Managers’ Intercultural Competence in Students’ Opinion - Pilot Study - Agnieszka Knap-Stefaniuk; Ewa Sowa-Behtane; Joan Sorribes (Journal of Modern Science)
Objectives The purpose of this article is to describe the importance of education in the development of intercultural competence of future employees and managers, from the students’ perspective. Current students will be future employees and managers, and many of them will work in multicultural teams, hence their opinion on the educational challenges related to developing intercultural competence is particularly important.